Species of Euglossa (Glossura) in the Brazilian Atlantic forest, with taxonomic notes on Euglossa stellfeldi Moure (Hymenoptera, Apidae, Euglossina) - Faria Jr.,Luiz R. R. (2007)
The species of Euglossa (Glossura) occuring in the Brazilian Atlantic forest were revised and an identification key to males and females is provided. The status of Euglossa annectans Dressler and E. stellfeldi Moure is reevaluated and the latter species is transferred from E. (Glossura) to E. (Glossurella). Here we also synonymize E. carinilabris Dressler under E. stellfeldi. Taxonomic notes are provided and relevant morphological features are illustred. Latitudinal color variation along the Brazilian Atlantic forest, found in two of the species studied here, is also presented and discussed.